4x+2-(x-3)=0

Simple and best practice solution for 4x+2-(x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+2-(x-3)=0 equation:


Simplifying
4x + 2 + -1(x + -3) = 0

Reorder the terms:
4x + 2 + -1(-3 + x) = 0
4x + 2 + (-3 * -1 + x * -1) = 0
4x + 2 + (3 + -1x) = 0

Reorder the terms:
2 + 3 + 4x + -1x = 0

Combine like terms: 2 + 3 = 5
5 + 4x + -1x = 0

Combine like terms: 4x + -1x = 3x
5 + 3x = 0

Solving
5 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 3x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 3x = 0 + -5
3x = 0 + -5

Combine like terms: 0 + -5 = -5
3x = -5

Divide each side by '3'.
x = -1.666666667

Simplifying
x = -1.666666667

See similar equations:

| 3(2a-1)=5 | | 4(5y-2)= | | 3x/4+1/2=1/4 | | 2(3a+1)=7 | | 3d-4-5d=7+d | | 8(3x+2)-4x=6 | | 8x+42b+544z=1000 | | 8x+2y=242 | | (2,8)5/2= | | 3a-(4b+2a)+5b= | | 3x^5-12x^4-45x^3+180x^2-48x+192=0 | | A=sw+w*w | | 5x-7+3x=7x-10 | | 5j+10=5 | | (9x^2+8x-2)+(-5x^2-7x+3)= | | 10x-5=12+6x | | P+0.02p=142.8 | | 25(xsqured-9)=25(x-3)(x+3) | | 8(3n+5)=8(9n+9)+6 | | In(x)=20 | | x+x*0.14=500 | | C=a+(n-8)dforn | | -6x-1=-6 | | 42/0.5= | | 2a+7=5a+9 | | 10r^2-2r=-4r+6 | | (x-6)*(x-6)=(x*x)-396 | | 45=2y | | 5x+43-2(x+7)=88-2x | | 0.16(y-2)+0.12y=0.20y-0.7 | | x^2-17X+3=0 | | 5x+43-2(x-7)=88-2x |

Equations solver categories